Constructing the mitochondrial genome of the Peruvian grunt Anisotremus scapularis Tschudi, 1846 (Lutjaniformes: Haemulidae) using RNA-seq data. Issue 2 (2nd April 2020) - Gomes-dos-Santos, André; Nande, Manuel; Espinoza-Ramos, Luis A.; Pepe-Victoriano, Renzo G.; Contreras-Mamani, Zumilda; Huanacuni, Jordan I.; Quispe-Mayta, J. Miguel; Fernández-Cárdenas, Cintia P.; Froufe, Elsa; Castro, L. Filipe C.
Abstract: Haemulidae is a widely diverse and widespread family of New World teleost fish. The Peruvian grunt, Anisotremus scapular, inhabits the South American Pacific coast where its overexploitation for human consumption. Fishing has led to the populational decline of the species and raised the need for conservation and aquaculture developments. Here we describe the complete mitogenome of the Peruvian grunt assembled from an RNA-seq dataset. The mitogenome length is 16, 785 bp and, as expected for a vertebrate, composed of 13 PCGs, 22 transfer RNA, 2 ribosomal RNA genes. Phylogenetic reconstruction, including all available 25 Lutjaniformes mitogenomes, places A. scapularis within the family Haemulidae, more precisely within the subfamily Haemulinae. Furthermore, paraphyletic relationships were observed within the other groups represented in the phylogeny. Overall, our results highlight the usefulness of using mitochondrial genomes for phylogenetic analysis in Haemulinae as well as the necessity to increase taxonomic sampling within the group.